Virus-like nanoparticles as a theranostic platform for cancer - Kim, Kyeong Rok; Lee, Ae Sol; Kim, Su Min; Heo, Hye Ryoung; Kim, Chang Sup (Frontiers in Bioengineering and Biotechnology, 2023)
Virus-like nanoparticles (VLPs) are natural polymer-based nanomaterials that mimic viral structures through the hierarchical assembly of viral coat proteins, while lacking viral genomes. VLPs have received enormous attention in a wide range of nanotechnology-based medical diagnostics and therapies, including cancer therapy, imaging, and theranostics. VLPs are biocompatible and biodegradable and have a uniform structure and controllable assembly. They can encapsulate a wide range of therapeutic and diagnostic agents, and can be genetically or chemically modified. These properties have led to sophisticated multifunctional theranostic platforms. This article reviews the current progress in developing and applying engineered VLPs for molecular imaging, drug delivery, and multifunctional theranostics in cancer research.